2014
DOI: 10.1177/1753944713516532
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and tumor necrosis factor alpha-inhibiting activity of sesame oil against doxorubicin-induced cardiotoxicity

Abstract: The chronic oral administration of sesame oil prevents acute doxorubicin-induced cardiotoxicity by enhancing cardiac endogenous antioxidants and decreasing myocardial TNF-α expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12]34 In our study, serum markers that indicate cardiac, hepatic, and renal damage increased significantly 4 days after 30 mg kg À1 DOX was administered, compared with the controls. In the light microscopic examination, histopathologic changes were seen in tissues of the DOX-treated rats.…”
Section: Discussionmentioning
confidence: 84%
“…[2][3][4][5][6][7][8][9][10][11][12]34 In our study, serum markers that indicate cardiac, hepatic, and renal damage increased significantly 4 days after 30 mg kg À1 DOX was administered, compared with the controls. In the light microscopic examination, histopathologic changes were seen in tissues of the DOX-treated rats.…”
Section: Discussionmentioning
confidence: 84%
“…Periasamy et al reported protection against sinusoidal obstruction syndrome by downregulating matrix metalloproteinase-9 expression, upregulating TIMP-1 expression, and inhibiting oxidative stress by a single prophylactic dose of sesame oil (23). Saleem et al demonstrated antioxidant and tumor necrosis factor alpha-inhibiting activity of sesame oil against acute doxorubicin-induced cardiotoxicity by enhancing cardiac endogenous antioxidants and decreasing myocardial TNF-α expression (24).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, daunorubicin is converted by intracellular endogenous enzymes into semiquinone that generating a free radical. [ 2 ] The heart is more vulnerable to oxidative damage due to less antioxidant enzyme activity (superoxide dismutase, glutathione, and catalase enzymes) consequently, accumulated free radicals leading to lipid peroxidation, mitochondrial membrane damage, injury of nucleic acid, and destruction of myocardium endoplasmic reticulum. [ 3 ] Moreover, the daunorubicin-induced release of cytokine-like tumor necrosis factor and interleukin 17 (IL-17) that lead to dilated cardiomyopathy and ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%